2014
DOI: 10.1103/physrevb.89.081408
|View full text |Cite
|
Sign up to set email alerts
|

Valence bond liquid phase in the honeycomb lattice materialLi2RuO3

Abstract: The honeycomb lattice material Li2RuO3 undergoes a dimerization of Ru 4+ cations on cooling below 270• C, where the magnetic susceptibility vanishes. We use density functional theory calculations to show that this reflects the formation of a 'valence bond crystal', with a strong bond disproportionation. On warming, x-ray diffraction shows that discrete three-fold symmetry is regained on average, and the dimerization apparently disappears. In contrast, local structural measurements using high-energy x-rays, sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
102
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 22 publications
(33 reference statements)
12
102
1
1
Order By: Relevance
“…2(b). Similar dimer formation was reported in other layered honeycomb compound Li 2 RuO 3 , of which origin is suggested to be the σ-like direct bonding between the neighboring Ru t 2g orbitals 19,20 . Since the dimer formation breaks the Ru t 2g degeneracy, we expect that SOC would not favor the dimer formation.…”
Section: A Effect Of Soc On In-plane Ru Dimerizationsupporting
confidence: 84%
“…2(b). Similar dimer formation was reported in other layered honeycomb compound Li 2 RuO 3 , of which origin is suggested to be the σ-like direct bonding between the neighboring Ru t 2g orbitals 19,20 . Since the dimer formation breaks the Ru t 2g degeneracy, we expect that SOC would not favor the dimer formation.…”
Section: A Effect Of Soc On In-plane Ru Dimerizationsupporting
confidence: 84%
“…The crystals are found to crystallize at room temperature in either the C2/m or the P 2 1 /m structures depending on synthesis conditions. However, in complete contrast to all existing polycrystalline work 20,23,24,26 , neither of these crystals show the magneto-structural transitions at high temperature. They instead show CurieWeiss behavior below 300 K and magnetic ordering at low temperatures into supposedly antiferromagnetic states 16 .…”
Section: Introductioncontrasting
confidence: 62%
“…The PDF analysis allows the tracking of short-ranged structural order. It was found that dynamically fluctuating dimers survive at temperatures well above the transition temperature T ≈ 540 K 23 . This suggests a scenario where a valence bond crystal in the low temperature phase melts into a valence bond liquid at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…1. Because of this static dimerization, the high-temperature structure with a nearly ideal honeycomb lattice, belonging to the space group C2/m, is reduced to a less symmetric structure with distorted honeycomb lattice belonging to the space group P 2 1 /m below T d [16,20,21]. Interestingly, this dimer transition is accompanied by a strong decrease of the magnetization.…”
Section: Introductionmentioning
confidence: 98%
“…In order to explain the origin of this transition, scenarios such as the transition from a highly correlated metal to a molecularorbital insulator accompanied by bond-dimer formation [20,22] and the formation of spinless dimers by magnetoelastic mechanism [23] have been proposed. More recently, a pair distribution function (PDF) analysis based on high-energy X-ray diffraction (XRD) revealed that the dimers exist even above T d but the positions of the dimers change dynamically [21]. Thus, the transition at T d can be regarded as the "melting" transition between the dimer-liquid and dimer-solid phases.…”
Section: Introductionmentioning
confidence: 99%